ANALISIS IMPLEMENTASI E-KINERJA PADA LINGKUNGAN PEMERINTAH KOTA BANDA ACEH - Rahmatika Latif, Ikhwan (Al-Ijtima`i: International Journal of Government and Social Science, 2021)
This article is research on the implementation of e-Kinerja within the Banda Aceh City Government. In this paper, the author uses a descriptive qualitative approach and collects data through a study of existing documents. This method illustrates how the implementation of e-Kinerja is carried out by the Banda Aceh Government, which the author then compares with existing concepts, namely the concept of performance and reward and punishment. The results of this study are that the implementation of the e-Kinerja system carried out by the Banda Aceh City Government has a good impact on the regional civil apparatus, the government, the City Government Work Unit (SKPK), and the public. These impacts include making promotions and transfers based on equal job for equal pay for regional civil servants, facilitating supervision for the government, and knowing the effectiveness and efficiency of work units.